Secrets of a Scottish isle - Neubauer, Erica Ruth, 1979- (Neubauer, Erica Ruth, 1979- Jane Wunderly mysteries., 2024)
Isle of Iona, 1927: Cast away on a remote locale, Jane's latest assignment depends on concealing her identity and blending in at an occult gathering. Not even her fiancé, Redvers, can be too close as she uncovers the truth about Robert Nightingale, enigmatic leader of the Order of the Golden Dawn--a group made up of supernatural ceremonies, influential people, and an undefinable darkness. When a woman tries to escape to the mainland only to be found murdered in the moors, the shocking scene reveals it's easier to join the Golden Dawn than it is to leave. Jane, set on solving the crime and catching the next ferry with Redvers, realizes she may be among the few still grasping reality. One high-ranking member searches for the killer by attempting to access otherworldly planes of existence, while others become immersed in a strange solstice ritual. Then there's Nightingale and the rivals who discarded him to start a new temple. As a second death brings fresh clues into focus, Jane needs to navigate a frightening dilemma--playing along won't help her crack the mystery, but revealing too much could be a fatal mistake...